BOOK REVIEW: MOBILE-MINDFUL TEACHING AND LEARNING: HARNESSING THE TECHNOLOGY THAT STUDENTS USE MOST - Mutiaraningrum, Ira (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Mobile-mindful Teaching and Learning: Harnessing the Technology that Students Use Most offers practical strategies for integrating mobile technology into teaching and learning. In addition to teaching procedures, this book provides access to online resources, such as applications tailored for mobile learning. It provides tangible examples to inspire readers, along with QR codes and a website to access additional resources for further exploration. With 11 chapters divided into three parts, this book skillfully incorporates opportunities for mobile learning to demonstrate the value of learning through smartphones while also acknowledging the fluid learning environments in which students engage, enabling the delivery of online modalities and features customized to specific needs and settings, regardless of time or location.